PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2021 - Nur Azizah Basmar; Jannati Tangngisalu; Bustam Bustam; Sri Wahyuningsih (JAKA (Jurnal Akuntansi, Keuangan, dan Auditing), 2023)
This study examines the impact of Return on Assets, Return on Equity, Debt to Equity Ratio, and Current Ratio on stock prices in the consumer goods industry sector on the Indonesia Stock Exchange. 53 companies are used as population. The sample adopted the purposive sampling method. With 35 companies as the sample that have met the sample criteria. The analysis used is multiple linear regression with the help of SPSS v.26 which is a research tool, the results of which show that Return On Assets and Return On Equity contribute positively and significantly to stock prices, while the Debt to Equity Ratio and Current Ratio contribute negatively and significantly to stock prices.